Presence of extensive Wolbachia symbiont insertions discovered in the genome of its host Glossina morsitans morsitans. - Corey Brelsfoard; George Tsiamis; Marco Falchetto; Ludvik M Gomulski; Erich Telleria; Uzma Alam; Vangelis Doudoumis; Francesca Scolari; Joshua B Benoit; Martin Swain; Peter Takac; Anna R Malacrida; et al. (Public Library of Science (PLoS), 2014)
Tsetse flies (Glossina spp.) are the cyclical vectors of Trypanosoma spp., which are unicellular parasites responsible for multiple diseases, including nagana in livestock and sleeping sickness in humans in Africa. Glossina species, including Glossina morsitans morsitans (Gmm), for which the Whole Genome Sequence (WGS) is now available, have established symbiotic associations with three endosymbionts: Wigglesworthia glossinidia, Sodalis glossinidius and Wolbachia pipientis (Wolbachia). The presence of Wolbachia in both natural and laboratory populations of Glossina species, including the presence of horizontal gene transfer (HGT) events in a laboratory colony of Gmm, has already been shown. We herein report on the draft genome sequence of the cytoplasmic Wolbachia endosymbiont (cytWol) associated with Gmm. By in silico and molecular and cytogenetic analysis, we discovered and validated the presence of multiple insertions of Wolbachia (chrWol) in the host Gmm genome. We identified at least two large insertions of chrWol, 527,507 and 484,123 bp in size, from Gmm WGS data. Southern hybridizations confirmed the presence of Wolbachia insertions in Gmm genome, and FISH revealed multiple insertions located on the two sex chromosomes (X and Y), as well as on the supernumerary B-chromosomes. We compare the chrWol insertions to the cytWol draft genome in an attempt to clarify the evolutionary history of the HGT events. We discuss our findings in light of the evolution of Wolbachia infections in the tsetse fly and their potential impacts on the control of tsetse populations and trypanosomiasis.